The Marketing-Happiness Paradox: Exploring Technological Consumer Behavior - Eduardo Ahumada-Tello; Esthela Galván-Vela; Rafael Ravina-Ripoll; Luis-Bayardo Tobar-Pesantez (Revista Empresa y Humanismo)
This study explores the marketing-happiness paradox in Mexico”s technology sector, analyzing consumer happiness driven by product consumption. Through structural equation modeling of survey data from 384 employees, it identifies internal and external happiness- related factors that propel a cycle of continuous consumption as consumers seek satisfaction in products with novel features. The findings emphasize the significant role of emotional impacts in marketing, suggesting strategies for technology companies. Initially relevant to the surveyed group, the study calls for broader research across various demographics. It presents a unique perspective on consumer behavior influenced by marketing, highlighting ethical and social concerns about leveraging consumer emotions in marketing practices.